2020
DOI: 10.1111/bjso.12422
|View full text |Cite
|
Sign up to set email alerts
|

Love is heterosexual‐by‐default: Cultural heterosexism in default prototypes of romantic love

Abstract: Cultural heterosexist ideologies assume heterosexuality to be the default norm. Four studies investigated when concepts of romantic love are heterosexual-by-default (N = 685). In Studies 1-2, participants generated features of romantic love, in general (i.e., the default prototype) or among one of three sexual orientation-specific couples (lesbian, gay, or heterosexual). Heterosexual-identified participants' default prototypes were more similar to heterosexual than same-gender prototypes (Study 1). Lesbian-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(86 reference statements)
1
1
0
3
Order By: Relevance
“…Research on stereotype content has found that stereotypes about sexual minorities are ‘gender inverted’ (Kite & Deaux, 1987; Klysing et al, 2021; Mize & Manago, 2018), and this experiment provides support that prototypes regarding sexual minority groups follow this same pattern. Furthermore, in line with previous research on representations of bisexuality (Mize & Manago, 2018; Morgenroth et al, 2021), both bisexual women and men were seen as more attracted to men than to women, a pattern which shows that androcentrism is present also in representations of romantic and sexual attraction (see Thorne et al, 2021 for additional discussion).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Research on stereotype content has found that stereotypes about sexual minorities are ‘gender inverted’ (Kite & Deaux, 1987; Klysing et al, 2021; Mize & Manago, 2018), and this experiment provides support that prototypes regarding sexual minority groups follow this same pattern. Furthermore, in line with previous research on representations of bisexuality (Mize & Manago, 2018; Morgenroth et al, 2021), both bisexual women and men were seen as more attracted to men than to women, a pattern which shows that androcentrism is present also in representations of romantic and sexual attraction (see Thorne et al, 2021 for additional discussion).…”
Section: Methodssupporting
confidence: 83%
“…both bisexual women and men were seen as more attracted to men than to women, a pattern which shows that androcentrism is present also in representations of romantic and sexual attraction (see Thorne et al, 2021 for additional discussion).…”
Section: Discussionmentioning
confidence: 96%
“…La H4 se ve confirmada parcialmente. Este resultado coincide con la literatura (Thorne et al 2021), mas al igual que otras hipótesis este tema no ha sido demasiado investigado. Se observa que en el colectivo heterosexual la interiorización de los mitos es significativa únicamente en comparación al colectivo bisexual.…”
Section: Discusión Y Conclusionesunclassified
“…La presencia de estas ideas ha sido estudiada sobre todo en adolescentes, pues se trata de una etapa que suele ir acompañada de la exploración de las relaciones románticas y, con ello, la construcción de la representación del amor (Bisquert et al, 2019;Masanet y Dhaenens, 2019). Se ha investigado tanto a nivel mundial como en población residente en España (Bisquert et al, 2019;Bonilla y Rivas, 2018;Bosch et al, 2019;Fernández et al, 2021;Masanet y Dhaenens, 2019;Thorne et al, 2021). No obstante, diversos estudios hablan de la vigencia de este discurso en población general (Bonilla y Rivas, 2018), y más concretamente en población adulta (Rodríguez et al, 2013); a pesar de que se reduzca con la edad según algunos/as autores/as .…”
Section: Introductionunclassified
See 1 more Smart Citation